Nutrient mineralization and soil biology as influenced by temperature and fertilizer management practices - Naher, Umme Aminun; Sarker, Imran Ullah; Jahan, Afsana; Md. Maniruzzaman,; Choudhury, Apurba Kanti; Kalra, Navin; Biswas, Jatish Chandra (Penerbit Universiti Kebangsaan Malaysia, 2019)
High soil temperature due to climate change may influence nutrient mineralization and soil biology. An incubation study was conducted at Bangladesh Rice Research Institute to determine the effect of temperature (28°C and 45°C) on nutrient mineralization and soil microbial population of two different soils (terrace and saline soil) having different nutrient management practices (chemical fertilizer and integrated nutrient management). Terrace soil was clay loam and saline (6 ds m-1) soil was sandy loam in texture. Total N and organic C content was significantly high in terrace soil compared to saline soil. High temperature (45°C) enhanced C mineralization by 33% in integrated nutrient management (INM) of terrace soil and 41% in chemical fertilizer treatment in saline soil. The NH4+-N mineralization was increased by 3 fold in saline soil at 45°C as compared to the same at normal temperature of 28°C. Temperature and nutrient management options also significantly influenced phosphorus (P) and potassium (K) mineralization. High temperature significantly enhanced P mineralization in INM compared to chemical fertilizer amendment. In terrace soil, at 28°C temperature K mineralization was high in chemical fertilizer amended soil as compared to INM treatment. Temperature and nutrient sources affected soil bacterial population significantly compared to fungi, and actinomycetes. Phosphate solubilizing bacteria (PSB) were more resistant to high temperature compared to free-living N2 fixing bacteria. In general, high temperature and nutrient management practices affected C, N, P, K mineralization and soil biology; although mode of action varied and depending on soil types and nutrient management practices.